ACUTE HEMATOGENIC OSTEOMYELITIS LITERATURE REVIEW - Berdiyarova Shokhida Shukurullaevna; Eshnazarova Ruxshona Olimjon qizi; Xakimova Zilola Alisher qizi; Jumanazarov Sardorbek Sanjar ugli (TADQIQOTLAR.UZ, 2024)
Annotation. Hematogenous osteomyelitis is one of the most severe purulent- septic diseases, leading to the development of severe sepsis with multiple organ failure, septic shock and death if delayed diagnosis and inadequate treatment. Improvements in diagnostic and treatment methods have made it possible to reduce the mortality rate in acute hematogenous osteomyelitis to 0.5-2.7% and the chronicity of the process to 3.1%, but orthopedic complications are still quite common with this pathology. Diagnosis of acute hematogenous osteomyelitis in children in the early stages of the disease presents certain difficulties, therefore, along with conventional diagnostics, the use of modern non-invasive diagnostic methods (ultrasound, CT) is very important.